Testing the static trade-off theory evidence from manufacturing firms listed in sri lanka - Jeyan Suganya, D.F. (University of Jaffna, 2019)
The major aim of the study is to investigate what extent Static Trade-off theory explains capital structure of manufacturing firms listed in Sri Lanka. According to the existing model developed for Static Trade-off theory, explanatory variables of this study are profitability, tangibility, size, non-debt tax shield and growth opportunity while leverage is considered as a dependent variable. Panel data has been collected from published financial statements of 20 manufacturing firms listed on Colombo Stock Exchange, Sri Lanka for the period from 2012 to 2016. Panel data regression analysis was employed to test the hypotheses of the study. Hausman specification test was performed to identify the best model among fixed effect and random effect model. Result revealed that random effect model was the best model for analysis. As per the random effect regression model, tangibility and non-debt tax shield have positive and significant impacts on leverage while rest of the variables in the model do not have significant impact on leverage. Result of the study concludes that Static Trade-off theory partially explains capital structure of manufacturing firms listed in Sri Lanka. Thereby, this study contributes to stakeholders of the non-financial institutions to find the essential factors should be taken into consideration when making financing decision on mix of capital structure of manufacturing firms listed in Sri Lanka.
Keywords: Capital structure; Leverage; Non-debt tax shield; Static trade-off; Tangibility